Analysis of nonlinear energy evolution in fractured limestone under uniaxial compression. (August 2022) - Wang, Guilin; Wang, Runqiu; Sun, Fan; Liu, Bolong; Zhang, Liang; Cao, Tianci; Li, Boyi
Highlights: The nonlinear energy self-promotion-inhibition model were proposed. The law of nonlinear energy evolution were proposed. The crack closure and propagation nonlinear behavior under UCS test were discovered. Threshold stress indicators for micro cracks' closure and propagation were proposed. Abstract: The development of dissolution underground results in the appearance of holes of different shapes in limestone, which affect its deformation and failure characteristics. Generally, the deformation and failure of the rock mass are accompanied by energy dissipation and release. To investigate the nonlinear energy evolution mechanism, a series of uniaxial compression and acoustic emission (AE) tests were conducted on limestone with holes of different shapes. Subsequently, based on the theory of nonlinear dynamics and rock micro-energy evolution, a nonlinear energy self-promotion-inhibition model and a nonlinear energy evolution law for limestone were proposed. The nonlinear energy self-promotion- inhibition model suggested an energy mechanism that could inhabit energy development, particularly when a critical failure occurred. In addition, the crack closure and propagation nonlinear behavior characteristics were investigated via a UCS test. Experimental results showed that energy promotion and inhibition occurred during loading, where the effect of the former was greater than that of the latter. Additionally, the energy promotion and inhibition effects of limestone with a "mushroom-shaped hole" were more significant than those of intact and other limestones. The "base" of limestone with a "dumbbell-shaped hole" reduced the stress concentration of the samples. Based on the nonlinear characteristics of the average growth rate of elastic strain energy density and the stress-time curve, the evolution of limestone with holes of different shapes under uniaxial compression can be categorized into five main stages, which can be further classified into seven substages based on the AE characteristics. Moreover, three threshold stress indicators, i.e., initial equilibrium stress, periodic crack growth stress, and chaotic initial stress, for describing the closure and propagation of microcracks were proposed. The results of this study reveal the nonlinear energy evolution mechanism of limestone with holes of different shapes and provide a basis for further research on the meso -evolution of rock mass.